Desain Kurikulum Merdeka Belajar dan Transformasi Evaluasi Pendidikan Agama Islam: Desain Kurikulum Merdeka Belajar dan Transformasi Evaluasi Pendidikan Agama Islam - Muhamad Syafiq mughni (CV. ALIM'SPUBLISHING, 2023)
This article was written to examine the new policy of the Ministry of Kemendikbud, namely the Kurikulum Merdeka Belajar Design, and its Implications for Evaluation of Islamic Religious Education Learning. The emergence of this new curriculum is due to the results of an assessment conducted by PISA (Programme for International Student Assessment) assessing that the quality of education in Indonesia is ranked 74th out of 79 countries. Broadly speaking, Indonesian education has experienced a very significant decline in literacy and numeracy. Starting from this phenomenon, the Ministry of Education and Culture designed a new curriculum design called independent learning. This study uses the Library Research method. Namely by collecting data and information in the form of texts, policy documents and previous studies on curriculum design in a formal institution. After studying the design of the Kurikulum Merdeka Belajar, this study analyses the implications of the Kurikulum Merdeka Belajar design with evaluation in Islamic religious education learning. The results of this study include, among others, that the new policy on the design of the Kurikulum Merdeka Belajar that will be applied in all formal education institutions in Indonesia is broadly as follows: 1) The national exam which previously only focused on the cognitive competence of students in the Kurikulum Merdeka Belajar has changed. become a minimum competency assessment that is held halfway through the education level process. 2) National standard school exams, which were formerly administered by the state, in this Kurikulum Merdeka Belajar were given to related educational institutions. 3) Simplification in compiling learning device documents. 4) Changes in the Zoning system in the admission of new students. Islamic religious education is a subject that is different from other subjects, this is because the learning process of Islamic religious education is coloured by divine spirits, from these divine spirits used to design an Islamic religious learning. Seeing the characteristics of the Kurikulum Merdeka Belajar that have been analysed above, the evaluation of Islamic religious education learning should be transformed into Authentic Assessment. In authentic research, Islamic education does not only assess students cognitively, but also assesses affectively (qolbiyah) and also morally (amaliyah).